The establishment and functioning of the garrison in a Prussian small town in the XVIII century (Königsberg/Chojna in East Brandenburg study) - Skrycki, Radosław (City and War, 2021)
In the 18th century, the Prussian State was undergoing a number of changes, most importantly related to the new conception of the role of the state in the social organisation and the role of the army within the state. The subordination of this first factor to the military matters caused a new vision of the army organisation, its recruitment and the disposition in fixed garrisons throughout the country. The wars, waged primarily by Frederic II, and later against a revolutionary France, had to be supported by an efficiently operating hinterland. Its element was the organization of fixed seats of regiments, that over time became an integral part of the urban organism. In the article, conditionings were discussed which laid at the roots of creating and organizing the garrison in a small city in the Eastern Brandenburg and subsequent alternations of stationed there regiments of the infantry. It’s important strategical positioning, close to the Pomeranian theatre of war (3rd Northern War), and later the Silesian one (three Silesian Wars) caused, that for an almost entire 18th century it was marked with the presence of a fixed garrison. This caused certain tensions with the townspeople, inevitable in a situation when every fifth man in town was a soldier; however, it created new development opportunities, which is indicated by almost the duplication of the population within a century and the considerable increase of the number of buildings.